Macroinvertebrate communities in streams with contrasting water sources in the Japanese Alps. Issue 14 (28th June 2020) - Milner, Alexander M.; Docherty, Catherine; Windsor, Fredric M.; Tojo, Koji
Abstract: Alpine streams are typically fed from a range of water sources including glacial meltwater, snowmelt, groundwater flow, and surface rainfall runoff. These contributions are projected to shift with climate change, particularly in the Japanese Alps where snow is expected to decrease, but rainfall events increase. The overarching aim of the study was to understand the key variables driving macroinvertebrate community composition in groundwater and snowmelt‐fed streams ( n  = 6) in the Kamikochi region of the northern Japanese Alps (April–December 2017). Macroinvertebrate abundance, species richness, and diversity were not significantly different between the two stream types. Community structure, however, was different between groundwater and snowmelt‐fed streams with macroinvertebrate taxa specialized for the environmental conditions present in each system. Temporal variation in the abundance, species richness, and diversity of macroinvertebrate communities was also significantly different between groundwater and snowmelt streams over the study period, with snowmelt streams exhibiting far higher levels of variation. Two snowmelt streams considered perennial proved to be intermittent with periodic drying of the streambed, but the macroinvertebrates in these systems rebounded rapidly after flows resumed with no reduction in taxonomic diversity. These same streams, nevertheless, showed a major reduction in diversity and abundance following periods of high flow, indicating floods rather than periodic drying was a major driver of community structure. This conclusion was also supported from functional analyses, which showed that the more variable snowmelt streams were characterized by taxa with resistant, rather than resilient, life‐history traits. The findings demonstrate the potential for significant turnover in species composition with changing environmental conditions in Japanese alpine stream systems, with groundwater‐fed streams potentially more resilient to future changes in comparison to snowmelt‐fed streams. Abstract : Macroinvertebrate communities in groundwater and snowmelt fed streams were investigated across the northern Japanese Alps. Unique community structures, and trait characteristics, were influenced by the environmental conditions in the two stream types. Macroinvertebrates inhabiting snowmelt fed streams may be at a greater risk from future climatic change in the region.